2012
DOI: 10.1371/journal.pone.0051394
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasites in Children from a Day Care Centre in Matanzas City, Cuba

Abstract: BackgroundIntestinal parasitic infections are widely distributed throughout the world and children are the most affected population. Day care centres are environments where children have proven to be more susceptible to acquiring IP.Methods and Principal FindingsA cross-sectional study was carried to determine the prevalence of intestinal parasites in stool samples among children who attend to a day care centre in an urban area of Matanzas city, Cuba, from March to June 2012. 104 children under five years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 20 publications
(25 reference statements)
8
43
3
5
Order By: Relevance
“…Children playing habit and the transmission way of the parasite, as this parasite is soil transmitted helminths, when children play they can easily acquire the infection. The result of Entrobeous vermicularis 2 (3.8%) was similar with study in Cuba 2 (1.9%) (Cañete, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Children playing habit and the transmission way of the parasite, as this parasite is soil transmitted helminths, when children play they can easily acquire the infection. The result of Entrobeous vermicularis 2 (3.8%) was similar with study in Cuba 2 (1.9%) (Cañete, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence was less than in previous studies conducted in different parts of Ethiopia namely, Wondo Genet, 85.1% (C, 2010), wonji, 24.3% (G/hiwot, 2014), Yergalem Hospital, 49.5 (Firdu, 2014) and Addis Ababa, 24.3%) (Adamu, 2006). This study also showed low prevalence as compared with studies conducted in different parts of the world like Cuba, 58.2% (Cañete, 2012), Pakistan, (52.8%) (Adeoye, 2007) and Kenya (25.6%) (Mbae, 2013). This difference could be due to the difference in geographical location, time of survey, diagnostic method difference and socioeconomic status.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…En el sector urbano, la prevalencia encontrada en este estudio es más baja que en el sector rural y menor que la reportada por Araya et al , no encontrándose otros estudios en sectores urbanos con los que comparar, por lo menos en esta última década. En ALC abundan estudios en sectores semiurbanos y urbanos en donde las prevalencias encontradas son variadas 5,31,32 , reportándose valores desde 28% hasta 83% aproximadamente, siendo la pobreza y la falta de estructura sanitaria los factores comunes asociados a esta condición. Similares reportes son encontrados en países africanos y asiáticos, donde las prevalencias en niños generalmente son altas, entre 66% a 98% aproximadamente en la mayoría de los estudios 33,34 , pero también se reportan prevalencias menores 35 .…”
Section: Discussionunclassified